ANALISIS UKURAN PERUSAHAAN, PROFITABILITAS DAN INFLASI TERHADAP NILAI PERUSAHAAN SEKTOR PROPERTI DAN REAL ESTATE YANG TERDAFTAR DI BEI - Tania Azzahra Arief, (2022)
Firm value is one of the factors seen by investors before making a decision to invest. The purpose of this research is to analyze the influence of independent variables which includeFirm Size, Profitability and Inflation to Firm Value in the listed property and real estate sectors on the Indonesia Stock Exchange in 2017-2021. The sample selection method used in this study is a purposive sampling method so there is 17 company property and real estate sectors on the Indonesia Stock Exchang as a sample. This study uses panel data regression analysis techniques. The results of this study found that: (1) Firm size have no effect on firm value (2) Profitability have a positive and significant effect on firm value (3) Inflation have no effect on firm value.